BASILICA Trial: One-Year Outcomes of Transcatheter Electrosurgical Leaflet Laceration to Prevent TAVR Coronary Obstruction. (19th May 2021) - Khan, Jaffar M.; Greenbaum, Adam B.; Babaliaros, Vasilis C.; Dvir, Danny; Reisman, Mark; McCabe, James M.; Satler, Lowell; Waksman, Ron; Eng, Marvin H.; Paone, Gaetano; Chen, Marcus Y.; Bruce, Christopher G.; et al.
Abstract : Background: Coronary artery obstruction is a rare, devastating complication of transcatheter aortic valve replacement. Transcatheter electrosurgical aortic leaflet laceration (Bioprosthetic or Native Aortic Scallop Intentional Laceration to Prevent Iatrogenic Coronary Artery Obstruction [BASILICA]) is a novel technique to prevent coronary artery obstruction. We report the 1-year outcomes of the BASILICA trial. Primary end points of 30-day success and safety have been reported previously. Methods: The BASILICA trial was a prospective, multicenter, single-arm safety and feasibility study. Subjects with severe native or bioprosthetic aortic valve disease at high or extreme risk for surgery, and high risk of coronary artery obstruction, were included. End points at 1 year included death, stroke, and myocardial infarction. Source data was independently verified and end points independently adjudicated. Results: Thirty subjects were enrolled between February 2018 and July 2018. At 30 days, BASILICA was successful in 28 subjects (93.3%), there were 3 strokes (10%), including 1 disabling stroke (3.3%), 1 death (3.3%), and 1 periprocedural myocardial infarction (3.3%). Between 30 days and 1 year, there were no additional strokes, no myocardial infarction, and 2 deaths (10% 1-year mortality). No subject needed repeat intervention for aortic valve or coronary disease. Two subjects had infective endocarditis (6.7%), but neither was isolated to the aortic valve. There were no hospital admissions for heart failure. Fourteen (46.7%) subjects required repeat hospital admission for other causes. Aortic valve gradients on echocardiography, New York Heart Association functional class, and Kansas City Cardiomyopathy Questionnaire scores improved from baseline to 30 days and were maintained at 1 year. Conclusions: In these subjects with multiple comorbidities and restrictive anatomy that underwent transcatheter aortic valve replacement, there was no late stroke, myocardial infarction, or death related to BASILICA. Mitigation of coronary obstruction remained intact at 1 year and was not related to recurrent readmission. These results are reassuring for patients and physicians who wish to avoid the long-term complications related to snorkel stenting. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03381989.